PENGARUH PERBANDINGAN TERIGU DENGAN TEPUNG KECAMBAH JAGUNG (Zea mays L.) TERHADAP KARAKTERISTIK FLAKES - Utama, I Dewa Gede Dwi Agastia; Wisaniyasa, Ni Wayan; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPADO - 10.24843/itepa.2019.v08.i02.p04, 2019)
This study aims to determine the effect of wheat flour ratio with corn sprouts flour on the characteristics of flakes produced and the exact composition of wheat flour with corn sprouts flour that is able to produce flakes with the best characteristics. The experimental design used was Completely Randomized Design with treatment factor that is the comparative treatment of flour with corn sprouts flour which consist of 5 levels: 50 %: 5 0%; 4 0%: 6 0%; 3 0%: 7 0%; 2 0%: 8 0%; 1 0%: 9 0% . The treatment was repeated 3 times to obtain 15 units of experiment. The data obtained were analyzed by variance and if the treatment had an effect on the observed variable then continued with Duncan test. The comparison of wheat flour with corn sprout flour significantly affected water content, ash content, fat content, protein content, carbohydrate content, coarse fiber content, tensile strength, color (hedonic test), aroma (hedonic test), texture (hedonic test and scoring ), taste (hedonic test) as well as overall acceptance (hedonic test) flakes. Comparison of 30% wheat flour : 70% corn sprouts flour produces flakes with the best characteristics, namely: water content was 2.94%, ash content was 2.99%, fat content was 11.60%, protein content was 14.40%, carbohydrate content was 68.08%, crude fiber content was 6.25%, tensile strength was 4.24 N, color liked, aroma some liked, texture crispy and liked, taste liked and overall acceptance liked.